Flow behaviour of an agitated tubular reactor using a novel dynamic mesh based CFD model. (2nd February 2020) - He, Yi; Bayly, Andrew E.; Hassanpour, Ali; Fairweather, Michael; Muller, Frans
Highlights: A new CFD model proposed for structure-structure and fluid-structure interactions. Soft-sphere collision model is combined with a dynamic meshing approach on Fluent. Agitator is mainly driven by contact force with external shaking tube. Pressure-strain term in RSM has a negligible effect on the motion of agitator. Majority of energy in ATR is dissipated by viscous rather than turbulent mechanisms. Abstract: Agitated tubular reactor (ATR) is an intensified continuous reactor in which radial mixing is decoupled from axial flow. This study proposed a novel CFD model to study fluid dynamics and mixing mechanisms in the ATR system. It combines a soft-sphere collision model with a dynamic meshing approach to tackle structure-structure and fluid-structure interactions (FSI) simultaneously. Its ability to handle FSI is validated on the sedimentation of a large sphere in a quiescent fluid. A periodic motion of the agitator was predicted, which is mainly driven by collision with the external oscillating tube. The fluid motion is complex, with vortex structures forming behind the agitator at its highest point; and the highest fluid velocities seen as fluid is squeezed under the agitator. Three Reynolds stress models were evaluated and the pressure-strain term shows little influence on the agitator's motion. Viscous dissipation was found to be the main mechanism for energy dissipation.